The transverse musculocutaneous gracilis flap for autologous breast reconstruction: focus on donor site morbidity - Siegwart, Laura; Fischer, Sebastian; Diehm, Yannick; Heil, Jörg; Hirche, Christoph; Kneser, Ulrich; Kotsougiani-Fischer, Dimitra (Breast cancer, 2021)
The transverse musculocutaneous gracilis (TMG) flap is as a valuable alternative in autologous breast reconstruction. The purpose of this study was to evaluate the donor site morbidity and secondary refinement procedures after TMG flap breast reconstruction.